RETROGRADE MULTI-CHARGE DUAL IMPLANTATION OF GaAs EPIC LAYERS ON MONO-Si SUBSTRATES - Novosyadlyy, S. P.; Bastrykin, S.V.; Pavliuk, Y. I.; Semenyshyn, A. D. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The article presents the results of experimental studies using multi-charge dual implantation of ions of different masses (silicon, sulfur, selenium) for the formation of retrograde concentration profiles of n + n of Schottky transistors, which increase the speed of LIC by 2.5-3 times.